CHLORITE DISSOLUTION IN THE ACID PH-RANGE: A COMBINED MICROSCOPIC AND MACROSCOPIC APPROACH - Brandt F.; Bosbach D.; Krawczyk-Barsch E.; Arnold T.; Bernhard G. (My University, 2003)
The dissolution of chlorite with intermediate Fe-content was studied macroscopically via mixed flow experiments as well as microscopically via atomic force microscopy (AFM). BET surface area normalized steady state dissolution rates at 25 °C for pH 2 to 5 vary between 10-12 and 10-13 mol/m2.s. The order of the dissolution reaction with respect to protons was calculated to be about 0.29. For pH 2 to 4, chlorite was found to dissolve non-stoichiometrically, with a preferred release of the octahedrally coordinated cations. The additional release of octahedrally coordinated cations may be due to the transformation of chlorite to interstratified chlorite/vermiculite from the grain edges inward.In-situ atomic force microscopy performed on the basal surfaces of a chlorite sample, which has been preconditioned at pH 2 for several months, indicated a defect controlled dissolution mechanism. Molecular steps with height differences which correspond to the different subunits of chlorite, e.g. TOT sheet and brucite like layer, originated at surface defects such or compositional inhomogenities or cracks, which may be due to the deformation history of the chlorite sample. In contrast to other sheet silicates, at pH 2 nanoscale etch pits occur on the chlorite basal surfaces within flat terraces terminated by a TOT-sheet as well as within the brucite like layer. The chlorite basal surface dissolves layer by layer, because most of the surface defects are only expressed through single TOT or brucite-like layers. The defect controlled dissolution mechanism favours dissolution of molecular steps on the basal surfaces compared to dissolution of the grain edges. At pH 2 the dissolution of the chlorite basal surface is dominated by the retreat of 14 Α steps, representing one chlorite unit cell.The macroscopic and microscopic chlorite dissolution rates can be linked via the reactive surface area as identified by AFM. The reactive surface area with respect to dissolution consists of only 0.2% of the BET-surface area. A dissolution rate of 2.5 x 10-9 mol/m2s was calculated from macroscopic and microscopic dissolution experiments at pH 2, when normalized to the reactive surface area.